2017
DOI: 10.1152/ajplung.00244.2017
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus infection alters ion channel function of airway and alveolar cells: mechanisms and physiological sequelae

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) and the amiloride-sensitive epithelial sodium channels (ENaC) are located in the apical membranes of airway and alveolar epithelial cells. These transporters play an important role in the regulation of lung fluid balance across airway and alveolar epithelia by being the conduits for chloride (Cl) and bicarbonate ([Formula: see text]) secretion and sodium (Na) ion absorption, respectively. The functional role of these channels in the respiratory tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 116 publications
3
40
0
Order By: Relevance
“…Taken altogether, these data demonstrate that in vivo IAV infection reduces Na + absorption (through ENaC) and Cl -/HCO 3 secretion (through CFTR) across mouse nasal epithelium transiently and consistently. This phenotype resembles that seen in patients with CF and COPD (13), which are known to be associated with altered airway rheology and mucociliary defects (14,15).…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Taken altogether, these data demonstrate that in vivo IAV infection reduces Na + absorption (through ENaC) and Cl -/HCO 3 secretion (through CFTR) across mouse nasal epithelium transiently and consistently. This phenotype resembles that seen in patients with CF and COPD (13), which are known to be associated with altered airway rheology and mucociliary defects (14,15).…”
Section: Resultsmentioning
confidence: 51%
“…Maintenance of the pulmonary mucosal barrier and gas exchange unit are critically dependent on intricate regulation of Na + absorption and Cland HCO 3 secretion via the ENaC and CFTR channels, respectively (reviewed in ref. 13). Previous studies have identified ENaC and CFTR channel dysfunction in response to IAV in various in vitro cell culture systems (24,25,35).…”
Section: Discussionmentioning
confidence: 99%
“…Bronchial epithelial cells (BEC) are a primary target for influenza virus replication [ 6 ]. Early response by BECs to influenza virus is crucial in determining progression of viral infection, adaptive immunity, and lung pathogenesis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Influenza virus infection may induce cell death in pneumocytes and damage the tight junctions, leading to fluid flooding into the alveolar space. 17,50,51 Also, the inhibition of epithelial ion channels (cystic fibrosis transmembrane conductance regulator and the amiloride-sensitive epithelial sodium channels) by influenza virus also accounts for the delayed alveolar fluid clearance 52,53 (►Fig. 1B, C).…”
Section: Innate Immune Cells Ards and Cytokine Stormsmentioning
confidence: 99%